Gastrointestinal tissue as a "new" target of pollution exposure. Issue 1 (21st July 2021) - Pambianchi, Erika; Pecorelli, Alessandra; Valacchi, Giuseppe
Abstract: Airborne pollution has become a leading cause of global death in industrialized cities and the exposure to environmental pollutants has been demonstrated to have adverse effects on human health. Among the pollutants, particulate matter (PM) is one of the most toxic and although its exposure has been more commonly correlated with respiratory diseases, gastrointestinal (GI) complications have also been reported as a consequence to PM exposure. Due to its composition, PM is able to exert on intestinal mucosa both direct damaging effects, (by reaching it either via direct ingestion of contaminated food and water or indirect inhalation and consequent macrophagic mucociliary clearance) and indirect ones via generation of systemic inflammation. The relationship between respiratory and GI conditions is well described by the lung‐gut axis and more recently, has become even clearer during coronavirus disease 2019 (COVID‐19) pandemic, when respiratory symptoms were associated with gastrointestinal conditions. This review aims at pointing out the mechanisms and the models used to evaluate PM induced GI tract damage.